Determination Prevalence of Stunting: Logistic Regression Analysis of Maternal and Child Health Factors - Setiyani, Astuti; Alfiah, Siti; Sumasto, Hary; Suparji, Suparji (National Journal of Community Medicine, 2026)
Background: Stunting remains a significant public health issue in Indonesia, with long-term impacts on child growth and development. Maternal and child health is considered a key factor during pregnancy and early childhood. This study aimed to investigate the association between maternal and child health practices and stunting in toddlers using logistic regression analysis. Methodology: A cross-sectional design was used in 140 mother-child pairs proportionally selected from four community health centers in urban Surabaya. Data were collected through a structured questionnaire, medical records, and anthropometric measurements. Statistical analysis was performed with a 95% confidence level, with significance determined at p <0.05. Results: Multivariable logistic regression analysis showed that routine antenatal care was a protective factor against stunting (OR = 0.136; 95% CI: 0.028-0.671; p = 0.014), indicating a substantially lower likelihood of stunting among children whose mothers attended regular ANC. Implementation of early initiation of breastfeeding was also independently protective (OR = 0.165; 95% CI: 0.032-0.852; p = 0.031). In contrast, complementary feeding before 6 months was the strongest risk factor for stunting (OR = 7.793; 95% CI: 2.486-24.432; p <0.001). Other variables were not statistically significant after adjustment. Conclusions: This study concluded that regular antenatal care and early breastfeeding are protective factors against stunting, while introducing complementary foods before 6 months of age carries significant risks. It is recommended that strengthening antenatal care (ANC) services, adherence to Early Initiation of Breastfeeding (IMD), and early initiation of complementary feeding (MP-ASI) be prioritized in stunting prevention programs.